The Effect Of Endorsements, Online Promotions On Social Media And Word Of Mouth On Buying Interest In Culinary Businesses In Palembang City - Annisa Auliya Azra; Diah Natalisa; Aslamia Rosa; Marlina Widiyanti (International Journal Labs, 2024)
This research was conducted with the aim of determining the influence of endorsements, online promotions on social media and word of mouth on buying interest in culinary businesses in the city of Palembang. The number of samples used in this study was as many as 125 respondents who were included in the sample with a homogeneous population type or the entire population in the same area by purchasing products of the same type or brand using the purposive sampling method. The results of multiple linear regression analysis show that endorsement, online promotion on social media and word of mouth have a positive and significant effect on buying interest. Endorsement, it is hoped that you can choose a foodvlooger who has a good image in the community, has quite a lot of followers on social media, a way to do food reviews that attract consumer interest. Promotions, it is hoped that MSMEs often provide promo prices by collaborating with several merchants such as e-wallets or banks that often provide discounts. Word of mouth, it is hoped that MSME culinary business actors in the city of Palembang can take advantage of the role of social media in promotional events.